Loss of protein kinase D activity demonstrates redundancy in cardiac glucose metabolism and preserves cardiac function in obesity - De Jong, Kirstie A. (Mol Metab, 2020)
OBJECTIVE: Protein kinase D (PKD) signaling has been implicated in stress-induced cardiac remodeling and function as well as metabolic processes including contraction-mediated cardiac glucose uptake. PKD has recently emerged as a nutrient-sensing kinase that is activated in high-lipid environments, such as in obesity. However, the role of PKD signaling in cardiac glucose metabolism and cardiac function in both normal and obese conditions remains unknown. METHODS: A cardiac-specific and inducible dominant negative (DN) PKD mouse model was developed. Echocardiography was used to assess cardiac function, while metabolic phenotyping was performed, including stable isotope metabolomics on cardiac tissue in mice fed either regular chow or a high-fat diet (43% calories from fat). RESULTS: Cardiac PKD activity declined by ∼90% following DN PKD induction in adult mice. The mice had diminished basal cardiac glucose clearance, suggesting impaired contraction-mediated glucose uptake, but normal cardiac function. In obesity studies, systolic function indices were reduced in control mice, but not in cardiac DN PKD mice. Using targeted stable isotope metabolomic analyses, no differences in glucose flux through glycolysis or the TCA cycle were observed between groups. CONCLUSIONS: The data show that PKD contributes to cardiac dysfunction in obesity and highlight the redundancy in cardiac glucose metabolism that maintains cardiac glucose flux in vivo. The data suggest that impairments in contraction-mediated glucose uptake are unlikely to drive cardiac dysfunction in both normal and metabolic disease states.